Transcriptional Regulation Mechanisms in Adaptively Evolved Pichia kudriavzevii Under Acetic Acid Stress - Sureeporn Dolpatcha; Huynh Xuan Phong; Sudarat Thanonkeo; Preekamol Klanrit; Nongluck Boonchot; Mamoru Yamada; Pornthap Thanonkeo (Journal of Fungi)
Acetic acid, a common weak acid in industrial fermentation processes, occurs naturally in lignocellulosic hydrolysates and is a byproduct of microbial metabolism. As a significant environmental stressor, it triggers the expression of multiple genes involved in various cellular responses, including biological processes, cellular components, and molecular functions. Using the acid-tolerant strain Pichia kudriavzevii PkAC-9, developed through adaptive laboratory evolution under acetic acid stress, we conducted a transcriptional analysis of 70 stress response-associated genes. RT-qPCR analysis revealed significant upregulation of several genes compared with the wild-type strain under acetic acid stress conditions. The most dramatic changes occurred in genes encoding key metabolic enzymes and stress response proteins associated with the TCA cycle (Fum: 18.6-fold, Aco: 17.1-fold, Oxo: 9.0-fold), carbon and energy metabolism (Tdh2: 28.0-fold, Erg2: 2.0-fold), electron transport chain (Gst: 10.6-fold), molecular chaperones (Hsp104: 26.9-fold, Hsp70: 13.0-fold, Sgt2: 10.0-fold), and transcriptional activators. Our findings indicate that the enhanced acetic acid tolerance of P. kudriavzevii PkAC-9 primarily depends on the coordinated upregulation of genes involved in energy metabolism, cellular detoxification mechanisms, and protein quality control systems through heat shock and transcriptional activator proteins.